Open wounds and unconcluded processes: the ghost of civil war and the events of january 2021 in the United States (Tempo e Argumento, 2022)
This article discusses the event of the Capitol invasion on January 6th, 2021 and relates it to the permanence in the present time of the collective traumas of the Civil War and the subsequent Reconstruction. The research analyzes these processes as unfinished and, therefore, “open wounds” in the political memory and social organization of the United States that, having crossed time, ended up determining the excluding character of representative democracy and perpetuating physical, psychological, and institutional violence against the black people of the country. The research had as its main primary sources the inaugural addresses of the presidents of the United States, analyzed in a long-term perspective and related to historiographical debates about democracy, racial segregation, and Civil War. The results point to the fact that, both at the end of the Civil War and in the process of Reconstruction of the country, the agreements between the white elites of the states prevailed over the expansion of citizenship for the black population, which has directly impacted the permanence of supremacist and anti-democratic ideas within American society.
Keywords: United States - History - Civil War, 1861-1865; segregation; United States - politics and government; democracy